Features of Women’s Language Used by Female Characters in Anne with an E Series - Widyasari, Ni Putu Fitri; Widiastuti, Ni Made Ayu; Qomariana, Yana (Universitas Jabal Ghafur, 2023)
This study investigates the women’s language features used by the female characters in Anne with An E series. The data source was taken from a series entitled Anne with An E. The data were obtained from the dialogue of the female characters. The qualitative research method was used to analyze the data in this research. Women’s language features proposed by Lakoff (1975) were applied in the analysis. The results show all the women’s language features are used by the female characters in Anne with An E series. They were lexical hedges, tag questions, rising intonation on declarative, empty adjectives, precise colour terms, intensifiers, hypercorrect grammar, super polite forms, avoidance of strong swear words, and emphatic stress. The results of this research have proven Lakoff's (1975) theory.Keywords: Women’s language features, female characters